(untitled) (Procedia of Social Sciences and Humanities, 2022)
Good posture is when the head, shoulders, spine, waist, knees and ankles are all in a straight line. Lack of awareness of students about the importance of maintaining good posture will cause bad posture which has the potential to trigger abnormalities in the spine. This community service program is one of the government’s efforts to improve the quality of life and productivity with good posture for students at SMA Muhammadiyah 3 Tulangan, Sidoarjo. This program is expected to increase awareness of good posture in students The method used in this activity is education with lectures, practice and demonstration methods by using teaching aids as a tool in the educational process. The props used when measuring posture using the postural zone and for practicing Mckenzie Exercise and Stretch for neck and shoulder pain using a mat and foam roller props. The success of this community service program for students can be seen from the increase in knowledge by 50%, increasing awareness of good posture in students by 75%, increasing the number of questions from students related to the material presented by 50% and the number of students experiencing a significant increase in pre-test and post-test scores by 70%.